Limited Effects of Set Shifting Training in Healthy Older Adults - Grönholm-Nyman, Petra; Soveri, Anna; Rinne, Juha O.; Ek, Emilia; Nyholm, Alexandra; Stigsdotter Neely, Anna; Laine, Matti (Frontiers in Aging Neuroscience, 2017)
Our ability to flexibly shift between tasks or task sets declines in older age. As this decline may have adverse effects on everyday life of elderly people, it is of interest to study whether set shifting ability can be trained, and if training effects generalize to other cognitive tasks. Here we report a randomized controlled trial where healthy older adults trained set shifting with three different set shifting tasks. The training group (n=17) performed adaptive set shifting training for five weeks with three training sessions a week (45 min/session), while the active control group (n=16) played three different computer games for the same period. Both groups underwent extensive pre- and post-testing and a one-year follow-up. Compared to the controls, the training group showed significant improvements on the trained tasks. Evidence for near transfer in the training group was very limited, as it was seen only on overall accuracy on an untrained computerized set shifting task. No far transfer to other cognitive functions was observed. One year later, the training group was still better on the trained tasks but the single near transfer effect had vanished. The results suggest that computerized set shifting training in the elderly shows long-lasting effects on the trained tasks but very little benefit in terms of generalization.